EVALUATION OF SEED COTTON YIELD AND SOME OF ITS COMPONENTE FOR UPLAND COTTON GENOTYPES, ESTIMATION OF SOME GENETIC PARAMETERS AND PATH COEFFICIENT ANALYSIS - K. M. Dawod; A. R. Al-Jumaily (Mesopotamia Journal of Agriculture)
Twenty genotypes of upland cotton were planted at Al-Haweja region under two spaces between rows (60 and 75cm) using split plots system in randomized complete block design with three replications to evaluate seed cotton yield and its components from other traits (plant height, number of fruiting branches, number of bolls per plant, seed index, boll weight, lint index and earliness), in addition to estimation of some genetic parameters and path coefficient analysis between seed cotton yield and its components. The results showed that 75cm row space gave 6.25% increase in seed cotton yield as compared with 60cm row space. Some genotypes was significantly superior than others for large number of traits including seed cotton yield. Lachata was the best variety, followed by Iranian 26 and IK378 and then IK259 and SP8886 varieties. Broad sense heritability ranged from (17.86%) for earliness and (83.78%) for plant height. Generally it was high for plant height, number of fruiting branches, number of bolls per plant, boll weight and lint index, moderate for seed index and low for the rest traits. It was shown that seed cotton yield had positive significant genotypic and phenotypic correlations with plant height, number of fruiting branches, boll weight, lint index and earliness. Path coefficient analysis revealed that earliness had high direct effect on seed cotton yield (genetically and phenotypically) and it was also significant in indirect effects through some other traits, followed by number of bolls per plant and boll weight phenotypically. This is important in possibility of these traits to use as selection indices for higher yield performance in breeding programs.